Nicotine dependence and neuropsychotic effects of varenicline - T. M. Bukatina; A. S. Kazakov; R. N. Alyautdin; T. V. Romanova; I. I. Snegireva (Безопасность и риск фармакотерапии)
Varenicline is a partial agonist of nicotinic acetylcholine receptors for the therapy of nicotine addiction. The efficacy and safety of the use of varenicline in the treatment of nicotine dependence have been demonstrated in clinical trial EAGLES. These studies describe adverse reactions such us mental disorders: depression, suicidal thoughts, suicidal behavior. However, data on the increase in the incidence of these adverse reactions during longer treatment with varenicline was not obtained. In 2016, the FDA has been presented with information about the risk of development the following serious neuropsychiatric adverse reactions on the using of varenicline: depression, manic syndrome, psychosis, hallucinations, delusions, homicidal ideation, aggression, agitation, anxiety, panic, suicidal ideation, attempt of suicide. These adverse reactions were observed in patients with and without psychiatric disorders.